The Impact of Social Media Influencers on Children’s Dietary Behaviors - Smit, Crystal R.; Buijs, Laura; van Woudenberg, Thabo J.; Bevelander, Kirsten E.; Buijzen, Moniek (Frontiers in Psychology, 2020)
Over the past years vlogs rapidly have become an attractive platform for food industries, sponsoring social media influencers to promote their products. As with more traditional media, social media influencers predominantly promote unhealthy drinks and foods that are high in sugar, fat, and salt—consumption of which may increase the risk of overweight, obesity, and noncommunicable diseases. The aim of the current Brief Research Report is to examine the impact of vlogs on children’s unhealthy dietary behaviors. Drawing on longitudinal survey data from 453 8- to 12-year-old children, we analyzed the longitudinal relations between children’s frequency of watching vlogs and their consumption of unhealthy beverages and snacks. Structural path modeling analyses of three waves of data with one-year intervals showed that children’s self-reported frequency of watching vlogs influenced consumption of unhealthy beverages two years later. The analyses did not yield significant relations for unhealthy snacks consumption. The strength of the observed longitudinal relation between children’s frequency of watching vlogs and consumption of unhealthy beverages was comparable to previous findings regarding more traditional types of food marketing.